2021
DOI: 10.1080/00223980.2021.1894411
|View full text |Cite
|
Sign up to set email alerts
|

Work-Sports Enrichment in Amateur Runners: A Diary Study

Abstract: Many employees worldwide combine a job with serious, goal-oriented ambitions in the athletic domain. However, scientific knowledge about day-today linkages between work and sports is lacking. We filled this gap in the literature by examining how experiences at work can enrich sports after work. Extending the work-home resources model to the work-sports interface, we posited that proactive work behaviors positively relate to work engagementa state that may permeate into the sports domain and relate to positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Situational resources can be obtained from individual situations such as marital relationships, employment relationships and social networks ( Brummelhuis and Bakker, 2012 ). Previous studies have explored the impact of workplace resources on work-family status from the perspectives of organizational culture, psychological climate, leadership, and post characteristics ( Wayne et al, 2004 ; Braun and Nieberle, 2017 ; Lee et al, 2017 , 2019 ; Almeida et al, 2018 ; Brosch and Binnewies, 2018 ; Rofcanin et al, 2018 ; Heras et al, 2020 ; Postema et al, 2021 ). Previous studies have explored the influence of individual resources on work-family status from the perspectives of body, emotion, job involvement and psychological capital ( Almeida et al, 2016 , 2018 ; Carlson et al, 2018 ; Matei and Vrg, 2020 ; Postema et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Situational resources can be obtained from individual situations such as marital relationships, employment relationships and social networks ( Brummelhuis and Bakker, 2012 ). Previous studies have explored the impact of workplace resources on work-family status from the perspectives of organizational culture, psychological climate, leadership, and post characteristics ( Wayne et al, 2004 ; Braun and Nieberle, 2017 ; Lee et al, 2017 , 2019 ; Almeida et al, 2018 ; Brosch and Binnewies, 2018 ; Rofcanin et al, 2018 ; Heras et al, 2020 ; Postema et al, 2021 ). Previous studies have explored the influence of individual resources on work-family status from the perspectives of body, emotion, job involvement and psychological capital ( Almeida et al, 2016 , 2018 ; Carlson et al, 2018 ; Matei and Vrg, 2020 ; Postema et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the impact of workplace resources on work-family status from the perspectives of organizational culture, psychological climate, leadership, and post characteristics ( Wayne et al, 2004 ; Braun and Nieberle, 2017 ; Lee et al, 2017 , 2019 ; Almeida et al, 2018 ; Brosch and Binnewies, 2018 ; Rofcanin et al, 2018 ; Heras et al, 2020 ; Postema et al, 2021 ). Previous studies have explored the influence of individual resources on work-family status from the perspectives of body, emotion, job involvement and psychological capital ( Almeida et al, 2016 , 2018 ; Carlson et al, 2018 ; Matei and Vrg, 2020 ; Postema et al, 2021 ). In this study, perceived supervisor support was used as work situation resource to enrich the content of work situation resource in W-HR model.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies additionally suggest that crafting behaviours in one life domain influences behaviours and experiences in other life domains. For example, Petrou and Bakker (2016) found that employees engaged in more leisure crafting when job demands and autonomy in crafting their home domain were high, while Postema et al (2021) showed that crafting behaviours at work spilled over into the sports domain of amateur athletes via their work engagement.…”
Section: The Link Between Job and Home Craftingmentioning
confidence: 99%
“…Although, engagement in physical exercise and healthy eating depends on many factors (Heikkilä et al, 2013;McDermott et al, 2016), work as a core life domain is particularly influential in fostering versus hindering health behaviors. For instance, a recent study showed that positive experiences at work such as work engagement are associated with better performance patterns in recreational runners (Postema et al, 2021). At the same time, work experiences -particularly when they are negative and stressful -can hinder physical exercise (Sonnentag & Jelden, 2009) and healthy eating (Liu et al, 2017).…”
mentioning
confidence: 99%
“…First, we suggest to directly measure enrichment and conflict between work and health behaviors. In the past, researchers based conclusions about enrichment and conflict mainly on empirical associations (e.g., correlations and regression weights) observed between work factors and health behaviors (Liu et al, 2017;Postema et al, 2021) but not on direct assessments of enrichment and conflict. While detecting empirical associations between work and health behaviors was important in uncovering this interesting phenomenon, researchers now need more direct assessments of enrichment and conflict to move the field forward.…”
mentioning
confidence: 99%